Attitudes, Awareness, and Usage of Medical Antiaging Treatments: Results of a Patient Survey - Weinkle, Susan (Matrix Medical Communications, 2010)
Objective: To explore factors important to patients considering medical antiaging treatments. Design: Ten-minute online survey using a global opinion panel. Setting: Survey of existing and prospective patients cosponsored by the American Society for Dermatologic Surgery and Dermik Laboratories, a business of Sanofi-Aventis U.S. LLC. Participants: 383 women aged 35 to 69 years (mean, 52 years; 91% Caucasian) with an annual household income of at least $50,000, who were considering undergoing medical antiaging treatments within the next two years (“medical antiaging treatment considerers”). Of these, 100 had used an injectable product such as dermal fillers, collagen replacers, or muscle relaxants in the past two years (“injectable users”); a subset of 64 had specifically used an injectable dermal filler or collagen replacer in the past two years (“filler users”). Measurements: Maximum difference analysis of factors most important to respondents when considering medical antiaging treatments, safety, and potential for side effects. Results: Medical antiaging treatment considerers, injectable users, and filler users all identified physician training and expertise as the most important factor (93–95% of respondents); other key factors included duration of effect, cost, how the product works, and recommendation by the physician. In paired comparisons, women were more interested in results that last a long time versus immediate results (89–91% of respondents), and gradual results that last for two years versus immediate results that last for six months (85–89% of respondents). Conclusion: Physician experience and training is very important to patients who are considering medical antiaging treatments, and should therefore be addressed during the counseling of prospective patients.